2021
DOI: 10.1002/advs.202101498
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Mediated Artificial Non‐Enzymatic Antioxidant MXene Nanoplatforms for Acute Kidney Injury Alleviation

Abstract: Acute kidney injury (AKI), as a common oxidative stress-related renal disease, causes high mortality in clinics annually, and many other clinical diseases, including the pandemic COVID-19, have a high potential to cause AKI, yet only rehydration, renal dialysis, and other supportive therapies are available for AKI in the clinics. Nanotechnology-mediated antioxidant therapy represents a promising therapeutic strategy for AKI treatment. However, current enzyme-mimicking nanoantioxidants show poor biocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 72 publications
3
42
0
1
Order By: Relevance
“…ROS levels at the wound site were examined on day 4 and day 17 after surgery using dihydroethidium (DHE) staining. [52,53] As expected, the diabetic wounds showed strong red fluorescence signals on day 4 and 17 postwounding, indicating that the diabetic wounds had high ROS levels (Figure 6d). As shown in Figure 6d,e, the red fluorescence signals in diabetic wounds showed a stark reduction after Nb 2 C@Gel treatment, while no such effect was noted in the Gel group.…”
Section: Nb 2 C@gel Decreases Oxidative Stress and Accelerates Diabet...supporting
confidence: 74%
“…ROS levels at the wound site were examined on day 4 and day 17 after surgery using dihydroethidium (DHE) staining. [52,53] As expected, the diabetic wounds showed strong red fluorescence signals on day 4 and 17 postwounding, indicating that the diabetic wounds had high ROS levels (Figure 6d). As shown in Figure 6d,e, the red fluorescence signals in diabetic wounds showed a stark reduction after Nb 2 C@Gel treatment, while no such effect was noted in the Gel group.…”
Section: Nb 2 C@gel Decreases Oxidative Stress and Accelerates Diabet...supporting
confidence: 74%
“…Interdisciplinary and cross‐application is the inevitable trend of future scientific development. [ 38 ] Precision medicine is the most popular concept in recent years. From diagnosis, treatment to prognosis, all aspects of medical treatment are looking for suitable ways to achieve precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al [ 86 ] reported the high scavenging activity of Ti 3 C 2 T x MXene against 2,2-diphenyl-1-picrylhydrazyl (95% in 10 min) at a low dose (0.06 mg mL −1 ). Furthermore, non-enzymatic antioxidant tactics based on MXene-based materials was illustrated for the treatment of diseases [ 87 ]. It was indicated that nanosheets of Ti 3 C 2 -polyvinylpyrrolidone demonstrated high biocompatibility and biodegradability as well as superb chemical reactivity toward multiple ROS for treating acute kidney injury [ 87 ].…”
Section: Biomedical Advancementsmentioning
confidence: 99%
“…Furthermore, non-enzymatic antioxidant tactics based on MXene-based materials was illustrated for the treatment of diseases [ 87 ]. It was indicated that nanosheets of Ti 3 C 2 -polyvinylpyrrolidone demonstrated high biocompatibility and biodegradability as well as superb chemical reactivity toward multiple ROS for treating acute kidney injury [ 87 ]. Several studies have been undertaken on antioxidant and scavenging properties of MXenes and MXene-based nanocomposites.…”
Section: Biomedical Advancementsmentioning
confidence: 99%